Design, Synthesis, and Characterization of 4-Undecylpiperidine-2-carboxamides as Positive Allosteric Modulators of the Serotonin (5-HT) 5-HT(2C) Receptor - Wild, Christopher T. (J Med Chem, 2018)
An impaired signaling capacity of the serotonin (5-HT) 5-HT(2C) receptor (5-HT(2C)R) has been implicated in the neurobehavioral processes that promote relapse vulnerability in cocaine use disorder (CUD). Restoration of the diminished 5-HT(2C)R signaling through positive allosteric modulation presents a novel therapeutic approach. Several new molecules with the 4-alkylpiperidine-2-carboxamide scaffold were designed, synthesized, and pharmacologically evaluated, leading to the discovery of selective 5-HT(2C)R positive allosteric modulators (PAMs). Compound 16 (CYD-1–79) potentiated 5-HT-evoked intracellular calcium release in cells stably expressing the human 5-HT(2C)R but not the 5-HT(2A)R cells. A topographically distinct allosteric site was identified based on the newly solved 5-HT(2C)R structure. Compound 16 modulated 5-HT(2C)R-mediated spontaneous ambulation, partially substituted for the training dose of the 5-HT(2C)R agonist WAY163909, synergized with a low dose of WAY163909 to substitute fully for the stimulus effects of WAY163909, and attenuated relapse vulnerability as assessed in a rodent self-administration model, indicating its therapeutic promise for CUD.